Kompetensi Guru Dalam Novel Pertemuan Dua Hati Karya Nh. Dini dan Novel Laskar Pelangi Karya Andrea Hirata: Kajian Sastra Bandingan - Ningsih, Hafsa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The aim of this research is to explain teacher competence in the novels Meeting Two Days and Laskar Pelenelitian. This is to explain qualitative descriptiveness using comparative literary methods. The peroli adaptation used is the theory of legislation. The data source for this research is the theory of Dua Hati and Laskar Pelangi. The data analysis technique is carried out by reading the two novels, marking the parts that show teacher competence, then classifying the data and finally concluding the data. Based on the research results, it was found that there was success in a teacher who had these four competencies in the stories told through the novels Meeting Two Hearts and the novel Laskar Pelangi. In both novels, each describes the competencies possessed by a teacher in the learning process. This is proven by the success that occurred in Waskito's character who turned into a good and obedient child because of Mrs. Suci's patience and persistence in guiding him. Apart from that, in the Novel Laskar Pelangi there is teacher competence in the characters Bu Mus and Pak Harfan. Thus, the two novels have something in common, namely the teacher competency possessed by the teacher character. The difference between the two novels is the number of different teacher characters. In the novel Two Day Meeting, there is only one teacher who is persistent and patient, namely Mrs. Suci. Meanwhile, in the novel Laskar Pelangi there are two teacher characters who are described as patient, loving and active, namely Mr. Harfan and Mrs. Mus with the full name Muslimah.